THE USE OF INFORMATION TECHNOLOGIES IN THE SPECIALIZED TRAINING OF STUDENTS OF ENGINEERING AND PEDAGOGICAL SPECIALTIES - Tsys Oleh; Arkhypov Ihor (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология, 2022)
The article deals with the problem of using information technologies in the process of specialized training of students of engineering and pedagogical specialties. The aim of the article is to reveal the essence and peculiarities of the use of information technology in the training of future vocational teachers; to identify the problems of classical teaching methods and to find ways to solve them through the use of information technology. A set of research methods was used, namely: content analysis, generalization and specification of the provisions of the Standards of Higher and Vocational Education of Ukraine, educational programs and curricula, designing the content and structure of an e-learning course, substantiation of the conditions for using e-learning courses in the process of specialized training of students. Results of the study. The Standard of Higher Education of Ukraine, specialty 015 Vocational Education (by specialization), first (bachelor) level, was analyzed. The existing curricula for the training of vocational teachers of transport profile were examined for their compliance with the requirements of educational standards. It has been determined that the normative part of the curriculum includes cycles of general and professional training which contain blocks of fundamental, psychological, pedagogical and methodological, scientific and subject, and practical training. It has been found out that the courses that form the special competencies of vocational teachers of transport profile belong to the block of scientific and subject training. The courses that form the special competencies of transport vocational teachers are highlighted, namely: vehicles and their maintenance, transport logistics, electrical and information-computer systems in transport, traffic rules, operation and repair of transport machine engines, interchangeability, standardization and technical measurements, and technical mechanics. Traditional approaches to the study of these courses are investigated in order to identify the main shortcomings. It has been stated that the traditional methodology of conducting classes involves significant time spent on note-taking of educational material, which can be mastered with greater efficiency using information and communication tools. Ways to eliminate the shortcomings of traditional approaches to the study of specialized courses are proposed, one of which is the development and implementation of e-courses on the Moodle platform, since this platform allows combining different formats of information, makes it possible to timely update the educational material in accordance with the pace of development of the transport industry, as well as it is easy to use and supported by most modern Smart devices. The structural and functional components of the e-learning course are defined including an information and organizational component; a training component; an information and reference component; and a practical component. The requirements for creating and implementing e-learning courses in the educational process are generalized. An e-learning course on the Moodle platform in the Transport Logistics course has been developed. It consists of information and methodological, training, control and evaluation, and reference blocks. A description of the content of these structural blocks is presented. Prospects for further research are identified; these are development of methods for using e-learning courses in specialized subjects in a mixed form of education under martial law.